LABOUR AND POLITICS IN CONTEMPORARY INDONESIA: THE CASE OF PARTAI BURUH (1999-2024) - Mahyudin, M. Alfan Alfian (JWP (Jurnal Wacana Politik), 2025)
This article reviews the presence and progress of the Labour Party in Indonesia in the Reformation Era (1999-2024). Labour and political dynamics in Indonesia have emerged since the Dutch colonial period. In the postcolonial era, the relationship between labour and politics was also dynamic. In the 1950s and 1960s they followed a political trend dominated by political parties. During Soeharto’s New Order political regime since the late 1960s, professional organizations, including labours, were not allowed to participate in politics. The state only approves one labour organization with limited space for movement. Entering the post-1998 Reform Era, labour organizations are no longer single, with the presence of several labour unions. Apart from that, the party experiment with a labour label is back. Even though it has mass numbers spread across many cities, the Labour Party has always failed to win seats in parliament. However, labour union actors continue to engage in politics, including by selling support for certain candidates in presidential elections. In fact, the Labour Party’s re-participation in the 2024 General Election also recorded its failure to become a political party that won seats in parliament (DPR/MPR). Why political experiments with party labels always fail in Indonesia in the Reformation Era is a question that will be answered in this research.